PENGARUH KETERAMPILAN KERJA, PENGALAMAN KERJA, DAN KOMPETENSI KERJA TERHADAP PRODUKTIVITAS KERJA PEGAWAI - Lupikasari, Sera; Pramutoko, Baju; Hendratmoko, Suseno (Commodities, Journal of Economic and Business, 2023)
The condition of the Indonesian economy has decreased due to external and internal factors of the country. As one of the government agencies, the Badan Pusat Statistik requires civil servants who contribute greatly in order to achieve the goals of the state in national development with maximum employee work productivity. To increase organizational productivity, employees must have the work skills, experience and competencies needed to provide quality services to colleagues and external stakeholders who have an interest in BPS organizations related to Kediri District. This research aims to determine the effect of work skills, work experience and work competence on employee work productivity at BPS Kediri District. The analysis technique uses validity test, reliability test, correlation test, multiple linear regression analysis, t test, F test. The population of this research is all 33 employees and a sample of 33 respondents using a saturated sample. The results of research at the BPS Kediri District show that the Variable of Work Skills (X1), Work Experience (X2), and Work Competency (X3) jointly affect the variable Work Productivity (Y) Sig value of 0.000 <0.05.